2015
DOI: 10.1016/j.ebiom.2015.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Host Protein Biomarkers Identify Active Tuberculosis in HIV Uninfected and Co-infected Individuals

Abstract: Biomarkers for active tuberculosis (TB) are urgently needed to improve rapid TB diagnosis. The objective of this study was to identify serum protein expression changes associated with TB but not latent Mycobacterium tuberculosis infection (LTBI), uninfected states, or respiratory diseases other than TB (ORD). Serum samples from 209 HIV uninfected (HIV−) and co-infected (HIV+) individuals were studied. In the discovery phase samples were analyzed via liquid chromatography and mass spectrometry, and in the verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 76 publications
5
70
0
1
Order By: Relevance
“…Hence, our data are consistent with the notion that a single biomarker will not be sufficient for distinguishing TB status in various patient groups (6,32). Further consistent with prior studies by us and others, we observed qualitatively different host responses in HIV coinfected compared with HIV uninfected TB patients (32)(33)(34), as well as quantitatively different Ab levels in proportion to extent of disease (6,34).…”
Section: M-hd-nappa -Conceptsupporting
confidence: 81%
“…Hence, our data are consistent with the notion that a single biomarker will not be sufficient for distinguishing TB status in various patient groups (6,32). Further consistent with prior studies by us and others, we observed qualitatively different host responses in HIV coinfected compared with HIV uninfected TB patients (32)(33)(34), as well as quantitatively different Ab levels in proportion to extent of disease (6,34).…”
Section: M-hd-nappa -Conceptsupporting
confidence: 81%
“…All of the significantly differentially expressed proteins from the baseline converter vs NI and LTBI vs NI comparisons were selected along with the most differentially expressed proteins from comparisons to active TB. We also included the significant proteins described in the MRM-MS assay of Achkar et al (2015).
Fig. 3Changes in plasma protein expression after TST-positive conversion.
…”
Section: Resultsmentioning
confidence: 99%
“…The ability to perform label-free quantification (LFQ) methods for an unbiased readout of novel targets reveals a better insight into the global cellular defects inherent in primary immune cells during disease states. These MS methods for the global quantification of proteins have allowed for the discovery of hundreds of candidate biomarkers of disease, demonstrated by a recent study of host protein biomarkers identifying active tuberculosis in HIV uninfected and co-infected individuals (52). In our study, we utilized this as a powerful discovery tool to assess the “per cell” defect of purified CD4+ T cells from HIV patients (S.…”
Section: Discussionmentioning
confidence: 99%